Population mortality impacts of the rising cost of living in Scotland: scenario modelling study - Neil Craig; Elizabeth Richardson (BMJ Publishing Group, 2023)
Introduction To inform policymaking, it is important to understand the population health impacts of recent increased inflation, and of measures implemented to mitigate these.Methods We used scenario modelling to estimate (a) how recent increased inflation would affect household incomes in Scotland, (b) how mitigation measures would modify these effects and (c) how mortality outcomes and inequalities in these would change as a result. Against a long-term average inflation scenario (baseline), we compared unmitigated recent inflation and inflation mitigated by UK Government support policies. We estimated differential price inflation by income quintile, based on the proportion of household spending on different goods and services. Using differential inflation rates, we estimated change in spending power (real income) for 2704 Scottish households in the 2015/16 Family Resources Survey, both with and without mitigating UK Government policies, and scaled these to the Scottish population. We estimated mortality effects using a cross-sectional relationship between household income and mortality, by deprivation quintile.Results Unmitigated price inflation was 14.9% for the highest income quintile and 22.9% for the lowest. UK Government policies partially mitigated impacts of the rising cost of living on real incomes, although households in the most deprived areas of Scotland would still be £1400 per year worse off than at baseline. As a result, even with mitigating measures in place, premature mortality was estimated to increase by up to 6.4%, and life expectancy to decrease by up to 0.9%. Effects would be greater in more deprived areas, and health inequalities would increase as a result.Conclusions Large and inequitable impacts on mortality in Scotland are predicted if real-terms income reductions are sustained. Progressive Cost of Living Support payments are not sufficient to offset the mortality impacts of the greater real income reductions in deprived areas.